2021
DOI: 10.1002/cpdd.1059
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, Safety, and Pharmacodynamics of Romiplostim in Chinese Subjects With Immune Thrombocytopenia: A Phase I/II Trial

Abstract: Romiplostim is approved for the treatment of immune thrombocytopenia (ITP). This study aimed to evaluate the pharmacokinetics, safety, and pharmacodynamics of romiplostim in Chinese patients with ITP. This multicenter, open-label, dose-escalation phase I/II trial enrolled ITP patients from 5 centers in China between October 2015 and August 2017. There were 2 cohorts: 1 μg/kg and 3 μg/kg weekly for 2 weeks. The end points included pharmacokinetics, platelet changes from baseline, hematological indicators, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…A previous study of eltrombopag showed that ethnicity affects the patient’s drug exposure [ 13 ]. A phase I/II trial [ 14 ] suggested that the pharmacokinetic features of romiplostim in the Chinese population are consistent with those in other ethnicities, but beyond pharmacokinetic data, the efficacy and safety remain to be confirmed in a phase III trial of romiplostim in China. Therefore, this phase III multicenter, randomized, placebo-controlled clinical study aimed to assess the effectiveness of romiplostim (starting dose of 1 μg/kg) as second-and-later-line treatment in Chinese adults with persistent or chronic ITP.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study of eltrombopag showed that ethnicity affects the patient’s drug exposure [ 13 ]. A phase I/II trial [ 14 ] suggested that the pharmacokinetic features of romiplostim in the Chinese population are consistent with those in other ethnicities, but beyond pharmacokinetic data, the efficacy and safety remain to be confirmed in a phase III trial of romiplostim in China. Therefore, this phase III multicenter, randomized, placebo-controlled clinical study aimed to assess the effectiveness of romiplostim (starting dose of 1 μg/kg) as second-and-later-line treatment in Chinese adults with persistent or chronic ITP.…”
Section: Introductionmentioning
confidence: 99%